Kristologi menurut Injil Yohanes [Christology According to the Gospel of John] - Patiung, Ksatria Londong (Diligentia: Journal of Theology and Christian Education, 2023)
The understanding of Christology is sometimes vague. Some think that Jesus only has the nature of God and does not have a human nature, while others think that Jesus is an ordinary human being. Therefore, believers must have a correct understanding based on the truth of God's Word. The Gospels testify about Jesus Christ and His ministry. This paper specifically explains Christology from the perspective of the Gospel of John with its uniqueness. The Gospel of John affirms the belief that Jesus is the Messiah and the Son of God (John 20:30-31). John emphasizes that Jesus has a special personal relationship with God that no one else has. In addition to affirming Jesus as the Messiah and the Son of God, John also affirms Jesus' recognition of Himself as the "Son of Man".  Therefore, all Christians should believe that Jesus is both true God and true man. BAHASA INDONESIA ABSTRACT: Pemahaman tentang Kristologi yang dimiliki orang Kristen kadang kala memiliki pemahaman yang kabur. Ada yang menganggap Yesus hanya memiliki natur Allah dan tidak memiliki natur manusia, ada pula yang menganggap Yesus sebagai manusia biasa. Oleh karena itu orang percaya harus memiliki pemahaman yang benar berdasarkan kebenaran Firman Allah. Kitab Injil menuliskan tentang Yesus Kristus dan pelayanan-nya. Tulisan ini khusus menjelaskan Kristologi dari sudut pandang Injil Yohanes dengan keunikannya. Injil Yohanes meneguhkan kepercayaan bahwa Yesus sebagai Mesias dan Anak Allah (Yoh. 20:30-31). Yohanes menekankan bahwa Yesus memiliki hubungan pribadi yang istimewa dengan Allah yang tidak dimiliki oleh siapa pun. Selain menegaskan Yesus sebagai Mesias dan Anak Allah, Yohanes juga menegaskan pengakuan Yesus akan diri-Nya sebagai “Anak Manusia”.  Untuk itu, semua orang Kristen harusnya memiliki kepercayaan bahwa Yesus adalah Allah sejati sekaligus manusia sejati.